Congestion control and its stability in networks with delay sensitive traffic. - Li, Y; Papachristodoulou, A; Chiang, M; Calderbank, A (2011)
We consider congestion control in a network with delay sensitive/ insensitive traffic, modelled by adding explicit delay terms to the utility function measuring user's happiness on the Quality of Service (QoS). A new Network Utility Maximization (NUM) problem is formulated and solved in a decentralized way via appropriate algorithms implemented at the users (primal) and/or links (dual). For the dual algorithm, delay-independent and delay-dependent stability conditions are derived when propagation delays are taken into account. A system with voice and data traffic is considered as example and the properties of the congestion control algorithm are assessed. © 2010 Elsevier B.V. All rights reserved.